Priority areas in the implementation of Payment for Environmental Services schemes: A scientometric analysis - Genuino , Luana Pessoa; Rodrigues, Sofia Suely Ferreira Brandão; Barbosa, Ioná Maria Beltrão Rameh; Carvalho, Vania Soares (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
Payment for Environmental Services schemes and programs emerge as economic instruments that aim to complement command and control instruments in environmental management. Due to their relevance and the need for allocation in places that can have the best performance, because they have a counterpart in financial resources, which are also scarce, research for the selection of priority areas is extremely important. To support researchers who aim to explore the line of research related to payment for environmental services, scientometric analysis presents the state of research in the area with measurement and quantitative analysis of bibliometric data, guiding the main sources and authors of reference and geolocating the scientific productions related to the subject. In the present research, a scientometric analysis and literature review was carried out with data from the Scopus and Web of Science databases, unifying the databases and analyzing the bibliometric information through the R-bilbiometrix interface, resulting in images, graphs, tables and maps that allowed an analysis of the state of the art and scientific research on the proposed theme. With the results, it was possible to observe the need for further studies on methodologies for selecting priority areas for PES schemes, as it is a fundamental tool for sustainable development